Pengaruh Fasilitas Kerja Dan Komuniaksi Kerja Terhadap Kinerja Aparatur Desa Di Kecamatan Kewapante Kabupaten Sikka - Maria Intan Pratiwi; Walter Obon; Viktor Eko Transilvanus (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research aimed to: (1) find out the description of administrations’ Performance, Work Facilities, and Work Communication on Village Administrations in the Kewapante sub-district (2) analyze the influence of Work Facilities and Work Communication on the Village Administrations’ Performance in the Kewapante sub-district, both partially and simultaneously. The population in this research was 32 people. This research was conducted through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. The descriptive analysis showed that the performance variables of administrations and work facilities were categorized as good enough while communication was categorized as not good. The t-test statistics showwed that partially the work facilities variable had a positive and significant effect on the official administrations’ performance. The results of the t-test statictic showed that partially the work communication variable had a signoficant and positive effect on the administration’s performance. The results of the f-test statistics showed that simultaneously the variables of work facilities amd work vommunication had a significant influence on the administrations’ performance. The results of the analysis of determination were able to explain the fluctuation of village administrations, performance in the Kewapante Sub-district by 47%.